El partido de ayer y de hoy / Gerardo Iglesias, Luis Lucio Lobato, José Sandoval - Lobato, Luis LucioSandoval, José (1913-2912); Iglesias, Gerardo (1945-)
Conferencias pronunciadas los días 27, 28, y 30 de mayo de 1985 en la Sede del Comité Central del PCE